Forest science research needs and priorities for sustainable forest management - Byron, R.N.; Sayer, Jeffrey A. (Crawford Fund, 1999)
The world is moving towards knowledge-based societies. Economies are globalising. The global public goods value of forests is being recognised at the same time that traditional role of state forest agencies in production forestry is declining, in part being taken over by multi-national corporations. At the same time emerging technologies are greatly enhancing our ability to assess and monitor forest attributes, to process and disseminate information and to enhance forest production. All of these changes will have an impact on how forest research is organised, what is done, who does it and who pays for it. It seems inevitable that much traditional forestry research concerned with sustainability and productivity enhancement at the stand-level will be taken over by private sector. However, there is going to be a major challenge in finding resources for research in support of the public goods values of forests at local, national and global levels. There is a widely-held view that we are in the midst of a world forest crisis. It s not a crisis of declining production but one of erosion of the 'public goods' or environmental values of forests. So far, we have not seen a concerted scientific response to the crisis, although the Inter-Governmental Panel on Forests (IPF) is seeking a new vision of forest science for the 21st century.